2017
DOI: 10.1016/j.joca.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Toward understanding the role of cartilage particulates in synovial inflammation

Abstract: Objective Arthroscopy with lavage and synovectomy can remove tissue debris from the joint space and the synovial lining to provide pain relief to patients with osteoarthritis (OA). Here, we developed an in vitro model to study the interaction of cartilage wear particles with fibroblast-like synoviocytes (FLS) to better understand the interplay of cartilage particulates with cytokines on cells of the synovium. Method In this study sub-10μm cartilage particles or 1μm latex particles were co-cultured with FLS ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 46 publications
(62 reference statements)
4
29
0
1
Order By: Relevance
“…In lapine, canine, and equine in vivo studies, injection of cartilage particles into the knee joint led to rapid development of synovitis followed by gradual onset of fibrotic synovium thickening and decreased cartilage thickness, similar to traditional animal models of OA such as ACL transection or meniscal release . Our group has also demonstrated that small CWP (<10 µm diameter) both attach to the cell membrane and are phagocytosed, and stimulate proteinase activity, cellular proliferation, collagen synthesis, and nitric oxide production in bovine FLS monolayer cultures …”
supporting
confidence: 61%
See 3 more Smart Citations
“…In lapine, canine, and equine in vivo studies, injection of cartilage particles into the knee joint led to rapid development of synovitis followed by gradual onset of fibrotic synovium thickening and decreased cartilage thickness, similar to traditional animal models of OA such as ACL transection or meniscal release . Our group has also demonstrated that small CWP (<10 µm diameter) both attach to the cell membrane and are phagocytosed, and stimulate proteinase activity, cellular proliferation, collagen synthesis, and nitric oxide production in bovine FLS monolayer cultures …”
supporting
confidence: 61%
“…Cells were expanded in α‐minimum essential medium (α‐MEM; Life Technologies, Carlsbad, CA) containing 10% fetal bovine serum, 1% antibiotic–antimycotic and 5 ng/ml fibroblast growth factor‐2 (Life Technologies) to obtain a homogenous FLS population of sufficient quantity. To create dense synovial monolayers, FLS at passage 3 were plated at 1.25 × 10 4 cell/cm 2 and cultured as previously described . Flow cytometry was performed as previously described to confirm that isolated cells maintained the characteristic FLS phenotype …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were cultured in αMEM containing 10% fetal bovine serum, 100 U/mL penicillin, 100 mg/mL streptomycin, and 5 ng/mL FGF (Life Technologies) for two passages to obtain a pure population of FLS (Sampat, O’Connell et al 2011, Silverstein, Stefani et al 2017). …”
Section: Methodsmentioning
confidence: 99%